Aplicación de instrumentos de gestión como contribución a la mejora productiva del sector minorista Agrícola del Cantón Bolívar. - Lozano Alcívar, Carlos Andrés (2018)
The main objective of the research is to apply management tools as a contribution to the productive improvement of the agricultural sector of Bolívar canton, to comply with the inductive method that allowed the analysis of the surveys made in the diagnosis, the method was also required in addition, the synthetic method was used to select and prioritize the main critical success factors (Capacity, Inventory, Process, Human Resources and Quality). Likewise, graphic techniques, documentary review and statistics were applied, for the analysis of data and the determination of action priorities, techniques for the study of critical success factors were identified through bibliographic review, techniques were selected relevant for the management and improvement of productive factors, and finally the techniques for each critical factor were applied, the method 20 * 80 with which it was obtained that dry hard corn is the most representative product of the area, the program of requirement of materials to know the amount of necessary supplies per hectare in a period of 6 months, the process map, process sheet and flowchart to classify, identify and accurately visualize the production process, the design of positions to determine the responsibilities and the HACCP standards the quality control of the product, determining that the crop performs in a prica, making it difficult to determine profits and recover the investment.